Description of Extraperitoneal Single-Port Robot-Assisted Radical Prostatectomy - Gupta, Radheshyam; Chaulagain, Ram Prasad; Shah, Binay Kumar; Lal, Nand; Ceesay, Essa; Xu, Wanhai (British Journal of Healthcare and Medical Research, 2023)
Extraperitoneal SP-RARP (single Port -Robot-assisted radical prostatectomy) is currently the standard minimally and safe invasive procedure for the surgical management of localized prostate cancer.When compared to open surgery, it has been demonstrated that the minimally invasive robotic approach provides comparable oncologic and functional outcomes with potential benefits, such as reduced blood loss, a shorter hospital stay, and a quicker recovery time. Due to its larger scope and early adoption, the transperitoneal RARP approach is typically the one used most frequently by robotic surgeons. The extraperitoneal approach has, however, been reported to have similar oncologic outcomes. Extraperitoneal RARP is less frequently used today because of its alleged technical complexity. However, this strategy has advantages, especially when peritoneal access is difficult due to severe adhesions from prior operations. To treat locally advanced prostate cancer, extraperitoneal SP-RARP is a feasible safe surgical option. Using the more recent single-port (SP) robotic system or the more traditional multiport robotic system, both transperitoneal and extraperitoneal approaches can be carried out. With regard to extraperitoneal RARP, the SP system has seen a rise in popularity due to its alleged benefits, which include better cosmesis, fewer postoperative analgesic and opioid needs, and a shorter length of hospital stay. For evidence supporting these benefits, additional research must be conducted.